Implementation and Performance Analysis of different Multipliers - Karki, Pooja; Yadav, Subhash Chandra (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*259.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956841);" role="presentation">Multipliers are very important and are used in various applications. This paper presents analysis of different <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*272.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980347);" role="presentation">multipliers design such as array multiplier, row bypassing multiplier and column bypassing multiplier. The <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*285.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01933);" role="presentation">multipliers are implemented using verilog HDL and the simulation is done in Modelsim simulator. The <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*298.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933263);" role="presentation">multipliers are compared in terms of delay and area. It is observed that delay in column bypassing multiplier is <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*311.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952659);" role="presentation">22.48% less than array multiplier and 21.25% less than row bypassing multiplier. It is also observed that the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*325.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919038);" role="presentation">column bypassing multiplier has less area than araay multiplier and row bypassing multiplier.